The Effect of Speed of Intervention in Hyperglycemic Emergencies on Patient Mortality - Tarigan, Indra (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Hyperglycemic emergencies, such as diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemia (HHS), are potentially fatal conditions if not treated immediately. The speed of medical intervention plays an important role in determining patient clinical outcomes, including the risk of mortality. However, there are still limitations in research on the relationship between the speed of intervention and patient mortality rates. This study aims to analyze the effect of the speed of medical intervention in hyperglycemic emergencies on patient mortality, as well as to determine the factors that contribute to patient clinical outcomes. This study used an observational analytical design with a retrospective approach to medical record data of patients with a diagnosis of hyperglycemic emergencies in the emergency unit of a hospital within a certain period. The main variables analyzed were the time of initial intervention after patient arrival and mortality. Data analysis was performed using descriptive statistics for univariate data and the chi-square test and logistic regression for bivariate and multivariate analysis. Univariate analysis showed that the majority of patients experienced a delay in intervention of more than 1 hour since arrival at the hospital. Bivariate analysis showed a significant relationship between the speed of intervention and patient mortality (p < 0.05). The results of logistic regression showed that patients who received intervention in less than 1 hour had a lower chance of dying compared to patients who received intervention later (OR = 2.5; 95% CI: 1.4-4.5). Other factors such as age, comorbidities, and initial blood glucose levels also have an effect on patient mortality. The speed of intervention in hyperglycemic emergencies has a significant effect on patient mortality. Faster intervention is associated with a decreased risk of death. Therefore, it is necessary to increase awareness of medical personnel regarding the importance of early detection and rapid response in treating patients with acute hyperglycemic conditions.